Theory of consumer behavior in the restaurant business - V. V. Dlusskaya; E. N. Kiseleva (Путеводитель предпринимателя, 2023)
Over the past two years, the food industry has faced many challenges. The situation around the world was repeated as the pandemic led to the cessation of the restaurant business and the introduction of quarantine restrictions. Although most restaurants have reopened and customers are returning, the industry is still facing challenges.As the pandemic progressed, consumers learned to cook more meals at home, leading to increased food consumption and a refusal to visit restaurants. Consumer behavior is a complex topic, it involves many different factors and aspects that influence each other and are interrelated, but these differences are often discussed separately. The restaurant business should provide quality services, a good brand image and improve the quality of food, in order to ensure customer loyalty.